Biological corridors as important habitat structures for maintaining bees in a tropical fragmented landscape (2020)
Biological corridors are an important conservation strategy to increase connectivity between populations—mainly vertebrates—in fragmented landscapes, which often require habitat restoration to achieve physical connections. Non-target groups such as bees could benefit from corridors while contributing to the restoration process given their role as pollinators, but little is known about the use of corridors by bees. Here we assessed the habitat value for bees of four biological corridors in the Colombian Andes by comparing bee species richness, community composition and functional diversity between corridors (which had two land-cover sections: riparian forest and restored forest), forest patches being connected by corridors and surrounding pastures. We found a higher species richness in riparian than in restored sections of corridors, which was comparable to that in forest and higher than in pasture. Community composition in forest and riparian sections were similar and differed from that in pasture. In contrast, functional diversity was similar among all land-use types, suggesting a higher species redundancy in forest and riparian corridors, given the higher species richness, compared to pastures. Our results show that riparian corridors are holding forest-associated species that could not survive in pastures, and given the higher redundancy, can significantly contribute to the maintenance of pollination services in fragmented landscapes. Our results also indicate that 13 years of restoration process have not been sufficient to reach reference levels (i.e. forest/riparian) in terms of bee species richness, but the recovery of some forest-associated species points to the potential of biological corridors to functionally connect forest patches. © 2019, Springer Nature Switzerland AG.